2011
DOI: 10.4187/respcare.01098
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Short-Term Intrapulmonary Percussive Ventilation in Patients With Bronchiectasis

Abstract: BACKGROUND: Treatment of bronchiectasis includes drugs, oxygen therapy, and bronchialclearance maneuvers. OBJECTIVE: To assess the safety and efficacy of intrapulmonary percussive ventilation (IPV) compared to traditional standard chest physical therapy in patients with bronchiectasis and productive cough. METHODS: In a randomized crossover study, 22 patients underwent, on consecutive days, IPV and chest physical therapy. Before each treatment session, immediately after the session, 30 min after the session, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(60 citation statements)
references
References 21 publications
1
58
0
1
Order By: Relevance
“…Those studies were of good, 26 fair, 16,19,20,42 and poor 30,40 quality for this outcome. One good study of Flutter in mechanically ventilated subjects, and one fair study of IPV in subjects with COPD reported improved oxygenation in the intervention arms.…”
Section: Oxygenation and Gas Exchangementioning
confidence: 86%
See 3 more Smart Citations
“…Those studies were of good, 26 fair, 16,19,20,42 and poor 30,40 quality for this outcome. One good study of Flutter in mechanically ventilated subjects, and one fair study of IPV in subjects with COPD reported improved oxygenation in the intervention arms.…”
Section: Oxygenation and Gas Exchangementioning
confidence: 86%
“…Paneroni et al evaluated IPV and CPT in a crossover RCT that included 22 subjects with bronchiectasis. 26 The mean age of the subjects was 64.4 Ϯ 8.9 years, and the mean percent-of-predicted FEV 1 was 53 Ϯ 30%. The IPV arm included 3 active cycles alternating high and low pressure for 30 min.…”
Section: Studies Evaluating Cpt In Non-postoperative Subjectsmentioning
confidence: 97%
See 2 more Smart Citations
“…Efficacy of percussive ventilation in clearing secretions relies on an asymmetric flow profile that favors expiration. 7 Using conventional frequencies in a 2 compartment test lung system, Volpe et al demonstrated parallel findings. 8 Differing compliances encouraged transfer of a mucus simulant from one ventilated test lung compartment to another across their shared carinal divider.…”
Section: Introductionmentioning
confidence: 91%